Restorative Justice as a tool to Prevent Crime as seen through Gandhian Lens - Shamota, Rahul; Sharma, Gaurika (Trinity Law Review, 2023)
Crime creates disbalance in society and to maintain harmony in society, there is an inherent need to maintain balance. Crime is considered to harm society and the offender is detained as a response to prevent more harm to society, this is called the preventive theory of the criminal system. But what about the harm already occurred? Crime has a multidimensional impact on society, affecting the community as a whole and the victim in particular, even the offender is affected by the same. The role of reformative justice becomes important here, generally speaking, to restore means “to return back” implying to reverse the effect that has taken place and bring the earlier position back. The majority of the credit for developing the philosophy of restorative justice goes to the western philosophers but in Indian Legal Jurisprudence it founds its strong ground in the Gandhian Philosophy of “ahinsa” meaning non-violence and always standing with the truth. In this article, the various dimensions of restorative justice will be discussed each viewed from the angle of the affected party, as no party that is affected by the crime has similar standing and a single principle of restorative justice will not be just and reasonable for all. The offender becomes the centre point and every individual in the criminal justice system just wants to come at him with his full strength and make him suffer, the state steps in the shoes of the victim and takes the responsibility to punish the offender on his behalf, in this whole process the victim remains hanging and becomes a ball being tossed from one person to another waiting for the time when he will land on the just ground. There is a serious need that the victim and the offender to get a chance to reconcile and harmonize and the offender gets a chance to be reintegrated again into society.
Keywords: Restorative Justice; Crime; Victim; Gandhian Philosophy